A9: Exploring Systemic Lupus Erythematosus from the Molecular Level and Dissecting the Disease Mechanism by Molecular Imaging. Issue Volume 66:Issue(2014)supplement 3 (March 2014) - Hu, Shaofan; Ke, Shi; Wang, Wei; Ran, Henry; Chen, Meipu; Zhang, Fujun; Qiu, Xiuchun; Jiang, Ming; Zou, Chaoxia; Zhang, Rufeng; Cao, Li; Fu, Rui; et al.
Abstract : Background/Purpose: One and a half million Americans suffer from systemic lupus erythematosus (SLE), with increased death rate in the 15–44 year age group. SLE has a wide range of symptoms and affects multiple organs and tissues. SLE affects each person differently over time. Treatment options are limited with potential serious side effects. There is no cure currently due to the lack of understanding of the mechanism of disease at molecular levels. However, recent developments in the field of molecular imaging provide a tool for noninvasive, target‐specific and longitudinal study of multiple disease components at the same time as well as understanding the dynamic change of the disease. We hypothesize genetic differences play a role in development and severity of the disease. In addition, multiple different disease molecules in different organs at one time point make SLE difficult to treat by standard regiments. Methods: We tested our hypothesis in animal models with two different genetic backgrounds and three target‐specific molecular imaging agents. Two groups of mice carrying normal or mutant Fas gene with SLE were utilized in the study. Optical imaging agents that specifically target to pro‐inflammatory cytokine (IL‐11), cytokine from T‐cells (CXCR4), or disease stroma (matrix metalloproteinase, MMP) were injected through the tail vein. Mice were imaged immediately after injection and for as long as 48 hours afterward. SAS software was used to analyze data by one‐way‐ANOVA or the general linear model. Data comparison was presented in notched box‐and whisker plots. The significant level was set at 0.05 with two‐tailed test. Results: Mice with a normal Fas gene have statistical higher signal intensities for all agents in the joint regions than the Fas mutant mice ( P = 0.0139). Target‐specific agents have different organ distributions in Fas mutant mice. The MMP signals are in the kidney (Fig. 1A) and IL‐11 signals are in the lung (Fig. 1B). Both agents have statistical low signal intensities in the same organs in the control mice with normal Fas gene (P<0.0002). The animal with normal Fas gene has high IL‐11 signal intensity in the knee (Fig. 1C). On contrary, CXCR4 has significantly low signal intensity in the Fas mutant mice. Fas mutant mice also have enlarged spleen and kidney by either size or weight than control mice (P<0.0001). Conclusion: We found that different genetic backgrounds predispose to different disease manifestations. Each organ has different disease components even with same the genetic background at the same disease stage The method we developed here can be used as a tool to better understand genetic and disease components and improve the treatment plan for individual patient needs.